2017
DOI: 10.1183/13993003.01871-2016
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre validation of the 1-min sit-to-stand test in patients with COPD

Abstract: Our aim was to comprehensively validate the 1-min sit-to-stand (STS) test in chronic obstructive pulmonary disease (COPD) patients and explore the physiological response to the test.We used data from two longitudinal studies of COPD patients who completed inpatient pulmonary rehabilitation programmes. We collected 1-min STS test, 6-min walk test (6MWT), health-related quality of life, dyspnoea and exercise cardiorespiratory data at admission and discharge. We assessed the learning effect, test-retest reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
122
3
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(169 citation statements)
references
References 41 publications
10
122
3
13
Order By: Relevance
“…The models for exacerbations were additionally adjusted for the number of exacerbations in the year before baseline. In the current analysis, we calculated estimates for handgrip strength per 1 kg and per 5 kg, and for the 1-min STS test per 1 repetition and per 3 repetitions, which has recently been suggested as the minimal important difference in COPD patients [8]. For mortality, we additionally calculated the area under the curve (AUC) for commonly used predictors and indices for mortality to compare their predictive discrimination abilities.…”
Section: Methodsmentioning
confidence: 99%
“…The models for exacerbations were additionally adjusted for the number of exacerbations in the year before baseline. In the current analysis, we calculated estimates for handgrip strength per 1 kg and per 5 kg, and for the 1-min STS test per 1 repetition and per 3 repetitions, which has recently been suggested as the minimal important difference in COPD patients [8]. For mortality, we additionally calculated the area under the curve (AUC) for commonly used predictors and indices for mortality to compare their predictive discrimination abilities.…”
Section: Methodsmentioning
confidence: 99%
“…Several measures of balance are available, and some have been used in PR programmes . Other measures of exercise ability such as the timed up‐and‐go test, sit‐to‐stand test and measures of arm strength and endurance focus on patients' ability to perform ADL. Most studies of these measures have been done among patients with COPD.…”
Section: Patient Assessment and Outcomes Measurement In Prmentioning
confidence: 99%
“…Therefore, in recent years the repetitive chair stand test, especially the 1-min sit-to-stand test, has become a popular method for rapid measurement of functional exercise capacity in patients with different chronic diseases including COPD and has even proven to be a predictor of mortality in patients with COPD. 37,38 Our findings regarding the 30sCST and the TUGT are novel, because to our knowledge no previous study has investigated the correlation between the PA of COPD patients and either of these two tests. The only comparable published data are for the 1-min sit-to-stand test, which demonstrated a moderate positive correlation with daily step count in patients with COPD in the study by van Gestel et al, 33 and for the five-repetition sit-to-stand test, which showed a lack of correlation with PA in a small study in 22 COPD patients published by Iwakura et al 39 Skeletal muscle mass wasting and/or dysfunction are present in about one-third of patients with COPD and have been associated with multiple negative implications, including exercise intolerance, higher health care use, reduced quality of life and increased mortality.…”
Section: Discussionmentioning
confidence: 85%